2018
DOI: 10.1055/a-0651-7817
|View full text |Cite
|
Sign up to set email alerts
|

Berufliche Gratifikationskrisen im Rettungsdienst – Eine Querschnittstudie zu Häufigkeit und Einflussfaktoren bei hauptamtlich tätigem Rettungsdienstpersonal

Abstract: The results demonstrates the need for preventive support and further research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 33 publications
1
7
0
1
Order By: Relevance
“…Thus, 33 studies were included in the review. As expected, more studies ( n = 22) were found on stress and strain [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ] than on behavior ( n = 6) [ 38 , 39 , 40 , 41 , 42 , 43 ] or well-being ( n = 5) [ 41 , 44 , 45 , 46 , 47 ]. Some studies were assigned to two categories: behavior/stress and strain [ 38 ], well-being/stress and strain [ 28 , 35 , 46 ], or behavior/well-being [ 41 ].…”
Section: Resultssupporting
confidence: 61%
See 4 more Smart Citations
“…Thus, 33 studies were included in the review. As expected, more studies ( n = 22) were found on stress and strain [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ] than on behavior ( n = 6) [ 38 , 39 , 40 , 41 , 42 , 43 ] or well-being ( n = 5) [ 41 , 44 , 45 , 46 , 47 ]. Some studies were assigned to two categories: behavior/stress and strain [ 38 ], well-being/stress and strain [ 28 , 35 , 46 ], or behavior/well-being [ 41 ].…”
Section: Resultssupporting
confidence: 61%
“…The studies were conducted worldwide. Most of the studies were performed in Europe [ 17 , 18 , 19 , 25 , 27 , 29 , 32 , 33 , 35 , 39 , 40 , 44 , 45 , 46 , 47 ]. Further studies came from Asia [ 20 , 23 , 26 , 36 , 38 , 41 ], Oceania [ 42 ], North America [ 21 , 22 , 28 , 30 , 31 , 43 ], South America [ 34 ], and Africa [ 24 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations